2000
DOI: 10.1029/1999jc000013
|View full text |Cite
|
Sign up to set email alerts
|

Physical and stable isotopic properties and growth processes of sea ice collected in the southern Sea of Okhotsk

Abstract: Abstract. This study presents physical and stable isotopic properties of sea ice in the southernmost section of the Sea of Okhotsk on the basis of observations and measurements made in 1995 and 1996 midwinter cruises. Structural analysis revealed that ice was predominantly of the granular type. Saucer-shaped cores and wedges were seen in the cross sections of the pancakes, which indicate a rafting event in the early stage of the pancake formation. The fraction of snow with respect to the total ice mass was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Only 15% of ice production occurs in first-year ice areas. These results are consistent with the field observations: Ukita et al (2000), and Toyota et al (2002), from an ice structural analysis, suggested that thickening of sea ice occurs mainly by rafting of thin sea ice formed in open water areas in the sea ice zone.…”
Section: Ice Productionsupporting
confidence: 91%
“…Only 15% of ice production occurs in first-year ice areas. These results are consistent with the field observations: Ukita et al (2000), and Toyota et al (2002), from an ice structural analysis, suggested that thickening of sea ice occurs mainly by rafting of thin sea ice formed in open water areas in the sea ice zone.…”
Section: Ice Productionsupporting
confidence: 91%
“…Jeffries et al ., ], was 7.5–9.7%. This compares reasonably well with observations from pack ice in the Sea of Okhotsk [ Ukita et al ., ], and landfast ice in both a Svalbard fjord [ Nicolaus et al ., ] and the Baltic Sea [ Uusikivi et al ., ]. In the only study in the high‐Arctic, on landfast sea ice in Baffin Bay, Kawamura et al .…”
Section: Resultsmentioning
confidence: 99%
“…To examine the ice growth processes, vertical sections were analyzed. Details of this analysis are described by Ukita et al [2000]. Briefly, we first made a thick section of 5‐mm thickness on glass plates to see the inclusions such as bubbles and brine pockets.…”
Section: Observationmentioning
confidence: 99%